2013
DOI: 10.1039/c3cp51396c
|View full text |Cite
|
Sign up to set email alerts
|

Specific interactions between the quaternary ammonium oligoether-based ionic liquid and water as a function of pressure

Abstract: The interactions between Ammoeng 100 and water are probed using high-pressure infrared measurements and DFT-calculations. The results of infrared absorption profiles suggest that the energetically favored approach for water molecules to interact with Ammoeng 100 is via the formation of anion-water interactions, whereas the alkyl C-H groups play much less important roles. After comparison with pure Ammoeng 100, it appears that no appreciable changes in band frequencies of alkyl C-H vibrations occurred as Ammoen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…This leads to the initial increase in contact angle values. The reduction in hydrophobicity observed at NFC:CHEC ratios of 25:75 may be attributed to the increased presence of quaternary ammonium groups that may interact strongly with both glycerol [40] and water molecules [41]. However, a simpler explanation may be due to the CHEC being the primary matrix component in the composites and both NFC and HEC displaying similar h values.…”
Section: Wetting and Barrier Properties Of Ppc-coated Nfc-chec Glycermentioning
confidence: 87%
“…This leads to the initial increase in contact angle values. The reduction in hydrophobicity observed at NFC:CHEC ratios of 25:75 may be attributed to the increased presence of quaternary ammonium groups that may interact strongly with both glycerol [40] and water molecules [41]. However, a simpler explanation may be due to the CHEC being the primary matrix component in the composites and both NFC and HEC displaying similar h values.…”
Section: Wetting and Barrier Properties Of Ppc-coated Nfc-chec Glycermentioning
confidence: 87%
“…Figure displays IR spectra recorded at ambient pressure of pure [BMI][PF 6 ] (Figure a) and [BMI][PF 6 ]/P123 mixtures having [BMI][PF 6 ] contents of 56 wt % (Figure b), 30 wt % (Figure c), 23 wt % (Figure d), and 13 wt % (Figure e). The absorption spectrum of pure [BMI][PF 6 ] exhibits two discernible peaks at 3127 and 3170 cm –1 , corresponding to coupled imidazolium C–H stretching vibrations. These imidazolium C–H stretching modes underwent changes upon adding P123, red-shifting to 3121 and 3165 cm –1 , respectively, in Figure b. Parts b–e of Figure also reveal the appearance of a shoulder peak near 3081 cm –1 .…”
Section: Resultsmentioning
confidence: 98%
“…Using pressure as a variable allows one to change intermolecular interactions in a controlled manner without encountering the major perturbations produced by changes in temperature or chemical composition. Previous studies of ionic liquids have indicated that high pressure can lead to phase transitions and, thereby, changes in physical properties. Russina et al and Su et al reported the structural organization and phase behavior, respectively, of 1-butyl-3-methylimidazolium hexafluorophosphate ([BMI][PF 6 ]) under high pressure. Conformational changes of the butyl chains in [BMI][Cl] at pressures of greater than 0.3 GPa have been observed using high-pressure spectroscopy .…”
Section: Introductionmentioning
confidence: 99%
“…The behavior of ILs mixed with polar solvents is of great interest from both a fundamental and industrial viewpoint, due to their amphiphilic character. Especially intriguing are aqueous solutions of ILs, the thermodynamic properties and microscopic assembly of which have been studied considerably . Despite these efforts, a deeper and more quantitative understanding of the molecular‐level structure is still needed.…”
Section: Introductionmentioning
confidence: 99%